Kepastian Hukum dalam Politik Hukum di Indonesia - Fadly Andrianto (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
This study aims to determine the development of legal certainty issues within the scope of law in Indonesia. This research uses normative juridical research methods. The results of the research are that in the discussion of the Second Amendment of the 1945 Constitution of the Republic of Indonesia NRI Article 28I (1) which contains legal certainty is basically proposed based on the political objectives of a particular group and does not answer the issue of legal certainty that actually occurs in Indonesia between positive law and customary law of the Indonesian people. The issue of legal certainty in Indonesia between positive law and customary law of the Indonesian people in its development was then resolved by Law Number 48 of 2009 concerning Judicial Power, namely in Article 5 paragraph (1) and Article 50 paragraph (1). Furthermore, with the enactment of Law Number 6 of 2014 concerning Villages. Current development regarding the issue of legal certainty in Indonesia is in the RUU KUHP.Keywords: Legal Certainty; Positive Law; Customary Law Abstrak Penelitian ini bertujuan untuk mengetahui perkembangan isu kepastian hukum dalam ruang lingkup hukum di Indonesia. Penelitian ini menggunakan metode penelitian yuridis normatif. Hasil penelitian yaitu bahwa dalam pembahasan Amandemen Kedua UUD NRI 1945 Pasal 28I ayat (1) yang memuat tentang kepastian hukum pada dasarnya diajukan berdasarkan tujuan politis suatu golongan tertentu dan tidak menjawab mengenai isu kepastian hukum yang sebenarnya terjadi di Indonesia antara hukum positif dan hukum adat masyarakat Indonesia. Isu kepastian hukum di Indonesia antara hukum positif dan hukum adat masyarakat Indonesia dalam perkembangannya kemudian diselesaikan dengan UU Nomor 48 Tahun 2009 tentang Kekuasaan Kehakiman yaitu dalam Pasal 5 ayat (1) dan Pasal 50 ayat (1). Selanjutnya dengan diundangkannya Undang-Undang Nomor 6 Tahun 2014 tentang Desa. Perkembangan saat ini mengenai isu kepastian hukum yang ada di Indonesia yaitu dalam RUU KUHP. Kata Kunci: Kepastian Hukum; Hukum Positif; Hukum Adat